The role of impurities and additives in the crystallisation of gypsum - Muryanto, Stefanus (Curtin University, 2002)
Scale formation is one of the persistent problems in mineral processing and related industries. One of the main components of the scale is frequently gypsum or calcium sulphate dihydrate (= CaS04.2H20). Gypsum is formed through the process of crystallisation, and it is well known that crystallisation process is significantly affected by the presence of admixtures. Industrially, scale formation occurs in an environment which is very rarely free from the presence of admixtures. In a typical mineral processing industry, certain types of admixtures are present, which may include metallic ions (e.g. originated from corrosion products) and certain types of the flotation agents used. The effect of admixtures on crystallisation kinetics and cyclical morphology can be very significant, even if they are present in trace amounts. It is important to emphasise that the effects are generally specific, that there is no unified theory that applies to all and every situation. The present study has investigated the effect of certain admixtures on gypsum crystallisation, and was accomplished in three phases of experiments: (1) seeded batch crystallisation; (2) seeded continuous crystallisation, and (3) once through flow system under isothermal condition. The three phases of the work used equimolar solutions of CaC12 and Na2SO4 to produce CaS04 which is the precipitating species. The seeded batch crystallisation experiment explored the effect of two flotation agents commonly used in mineral processing plants: (1) sodium isopropyl xanthate (= SIPX) and, (2) isopropyl thionocarbamate. The experiments were performed at 25, 35, and 45°C, respectively. The initial concentration of the crystallising solution was 2,000 ppm of Ca 21 and it reached the equilibrium concentration values of between 1,000 and 8,00 ppm of Ca 2+ in 90 minutes.The effect of the two selected admixtures on crystallisation was measured by continuous monitoring of the desupersaturation of the crystallising solution with time, which subsequently resulted in the determination of the crystallisation rate constant. The results arc as follows. Firstly, the admixtures selected (either individually or in combination) were able to retard the growth rate of gypsum. In the absence of any admixture, the second order rate constant was between 1,405 x 10-6 and 1,561 x 10-6 ppm-1 min-1. Addition of SIPX at a typical plant dosing level 0.200 g/L) reduced the rate constant to 475 x 10-6 PPM-1 min', while isopropyl thionocarbamate at a typical plant dosing level (= 0.070 g/L) decreased the rate constant to 254 x 10-6 ppm-1 min-'. However, addition of a combination of the two admixtures, each at a typical plant concentration level, reduced the rate constant to 244 x 10-6 ppm-1 min-1, which was only slightly below that in the presence of isopropyl thionocarbamate. Thus, in these batch crystallisation studies, isopropyl thionocarbamate seemed to be dominant over SIPX. Secondly, the batch crystallisation system in the current work did not show any induction time. It was concluded that the seeds added into the batch system could be capable of eliminating the induction time. Thirdly, the reduced growth rate of the gypsum crystals as affected by the admixtures was probably caused by the adsorption of admixtures onto the crystal surface. The second phase of the project involved a seeded continuous (MSMPR) crystalliser. Some parameters used in this experiment (mean residence time, agitation speed and type of one admixture) were taken from the batch experiment carried out in the first phase of the project.Three admixtures were chosen for the seeded continuous crystallisation: (1) SIPX, (2) Fe3+, (3) Zn2-, and they were used either individually on in combination with each other. SIPX was chosen as it is one of the most common flotation agents used in mineral processing. Metallic ions: Fe3+ and Zn2+ were selected, since they were found in substantial amounts in both scale samples and process water in certain minerals processing industries. In general, the admixtures tested were found to be able to inhibit the crystal growth rates, but to enhance the nucleation rates. In addition, the growth rate was found to be dependent on crystal size, and hence, a correlation between these two parameters and the admixture concentration was formulated. For a fixed level of concentration (f 700 ppm of Ca z+ at steady state) and crystal surface area, it was proved that for each crystallisation temperature: 25 and 40°C, the correlation function can be represented as G = k Lα (1 +C)β where: G = linear growth rate, micron/hour; k, α, and β = dimensionless constants; L = (sphere equivalent) crystal size, micron; C = concentration of the admixtures used, ppm. For both the crystallisation temperatures used, the correlation function shows that the growth rate is significantly dependent on crystal size, but a weak function of admixture concentrations. The mechanism of crystal growth inhibition was assumed to be that of adsorption of admixtures onto the active growth sites, thereby decreasing or stopping the growth. Similar to the first phase of the present study, this seeded continuous crystallisation also showed no induction time. The third phase of the project investigated the gypsum scale formation in a oncethrough pipe flow system under isothermal condition and in the presence of admixtures.Four types of pipe materials were tested: PVC, brass, copper and stainless steel. Two admixtures were selected: SIPX and Fe3+. The behaviour of the gypsum scale formation was measured as the mass of the gypsum scale deposited on the substrate per unit area of the pipe surface. Within the range of the experimental conditions applied in this scale formation study, the following results were obtained. Firstly, the mass of the gypsum scale increased with concentration (in the range: 2,000 to 6,000 ppm of Ca t+) and that the correlation between the mass and the concentration can be represented by quadratic functions. Secondly, the mass of the gypsum scale decreased with increasing concentration of the admixtures used. Thirdly, the flow rate of the scaling solutions (in the range: 0.4 to 1.3 cm/sec) did not significantly affect the mass of the gypsum scale. PVC produced the highest mass of gypsum scale, followed by brass, copper, and stainless steel, respectively. Fourthly, the presence of admixtures caused the surface of the scale deposit to become rougher than was the case in a pure system, and longer scaling experimental times resulted in denser scale deposits. In this scale formation project, the induction time was investigated. In contrast with the first and the second phase of the projects, the induction time in the scale gypsum formation experiment was significant. At a concentration of 2,000 ppm of Ca 2+' pure gypsum solutions had induction times of about 105 minutes at 18.3°C and 97 minutes at 20.3°C. In the presence of 10 ppm of SIPX, the scaling solution at 2,000 ppm of Ca2+ and 19.2°C had an induction time of 1,400 minutes. The present study produced three important findings.Firstly, the presence of Fe 3+ or sodium isopropyl xanthate (SIPX) reduced the growth rate of gypsum crystallised either in a vessel (= a continuous crystalliser) or in a pipe flow system. Secondly, the rate of growth of gypsum crystals was found to be consistently higher in the vessel than in the pipe flow system. The rate of growth of the pure gypsum in the crystalliser at 25°C was 0.0389 kg/ m2 hour while those in the pipe flow system were between 0.0289 and 0.0202 kg/m2 hour, depending on the pipe material and the scaling solution flow rate. Thirdly, with respect to gypsum scaling, PVC was the least favourable material, followed by brass and copper, while the most favourable was stainless steel. It is believed that the present study has significantly contributed to the understanding of the effect of admixtures on crystallisation of gypsum, especially in relation to the scale formation.